Prace parlamentarne nad projektami ustaw reprywatyzacyjnych w Senacie I i Sejmie X kadencji - Korzeniowska-Lasota, Anna (PRAWO i WIĘŹ, 2024)
The political changes that took place after 1989 gave hope to many citizens for regaining their lost property, both that related to the post-war change of the state’s eastern border and taking over property without compensation. And although the issue of re-privatization was present in the political discourse, it caused so much controversy that, despite the legislative initiatives undertaken, it was not comprehensively regulated. The paper presents drafts of reprivatization laws on which the Senate of the 1st term of office and the Contract Sejm worked. It presents the parliamentary discussion surrounding the issue of reprivatization and the most important problems that caused the work on all the acts submitted in the Sejm of the 10th term to fail.